KAJIAN STATISTICAL DAN COST EFFICIENCY DALAM PENENTUAN GUGUS SAMPEL BLOK SENSUS TERBAIK (Studi Kasus: Sampling Design Susenas-2015 di Kabupaten Natuna) - Wiwik Andriyani Lestari Ningsih; I Made Arcana (MEDIA STATISTIKA, 2018)
Two aspects of efficiency that should be considered in applying sampling design of a survey are statistical efficiency and cost efficiency. Efficiency in statistical aspect improves precision of estimators obtained by the survey data, whereas efficiency in cost aspect provides an economic survey. The purpose of this researchis to evaluate the both efficiencies in all possible census blocks (CBs) sample setand to identify the best CBs sample set in the 2015 National Socio-Economic Survey (Susenas). Therefore, a computer program for calculating statistical, and cost efficiency aspects was developed in this research to determine the best sampel set of  CBs among all possible sampel set of CBs based on sampling design of the 2015 Susenas implemented in Natuna District, Kepulauan Riau Province. The best possible sample set of CBs is determinedby considering statistical efficiency aspect, cost efficiency aspect, as well as combination of those two aspects. The result showed that the best sample set of CBs on statistical efficiency aspect provided the CBs sample set having minimum value of RSE index; evaluation on cost efficiency aspect provided the best CBs sample set having minimum value of total cost esimated using the total score of accessibility index; and evaluation on both efficiency aspects provided the best CBs sample set having minimum value of RSE index and minimum value of total score of accessibility index. Keywords: sampling design, all possible samples, statistical efficiency, cost efficiency